Ayat - ayat Al-Qur'an Tentang Keseimbangan Dunia dan Akhirat : Relevansi dalam Manajemen Waktu - Ferizal Ferizal; Zahra Salsabila Polem; Az Zahra Salsabila Lubis; Aulia Rizky Lubis; Ananda Amelia; Khairuvi Jannatu Sabila BR Pasaribu; Selvi Ayu Berutu; Muhammad Lutfy Adly (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the verses of the Qur'an that emphasize the balance between the world and the hereafter and their relevance in students' time management. Using a qualitative approach, this study involved UIN Tuntungan students as respondents to analyze how Islamic values are applied in their daily lives. The results showed that the majority of students have a high level of awareness of carrying out obligatory worship, but still face challenges in managing time for worldly activities and worship. The use of technology and daily planning are important factors in creating this balance. This study provides strategic recommendations for improving time management based on spiritual values.